(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2013)
The plethora of treatment modalities available for the treatment of female stress urinary incontinence reflects the uncertainty in the pathophysiology of this condition and the mechanism of cure. No single treatment method is suitable for all patients. For best results, many factors must be considered before choosing the treatment method most suited to the particular patient. This review examines the various treatment options available and attempts to set out criteria for choice of treatment. The role of conservative treatment has been deliberately highlighted especially for young and well motivated women with mild to moderate urinary stress incontinence before surgical treatment is used. The role and limitations of well established surgical procedures like Burch colposuspension and urethroplasty and the most recently introduced procedures like TVT/TOT,collagen implants ,laparascopic colposuspension and the role of artificial urinary sphinter are also examined DOI: http://dx.doi.org/10.3329/bjog.v26i1.13759 Bangladesh J Obstet Gynaecol, 2011; Vol. 26(1) : 37-44